2013
DOI: 10.1121/1.4821214
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of complex acoustic intensity in an acoustic waveguide

Abstract: Acoustic intensity is normally treated as a real quantity, but in recent years many articles have appeared in which intensity is treated as a complex quantity where the real (active) part is related to local mean energy flow, and the imaginary (reactive) part to local oscillatory transport of energy. This offers the potential to recover additional information about a sound field and then to relate this to the properties of the sound source and the environment that surrounds it. However, this approach is applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…The reason for this discrepancy is the approximation inherent in the volume velocity matching conditions used for the inlet and outlet plane of the blockage in the plane wave model. This is confirmed by comparing plane wave predictions with a full finite element model [20,21], which is also shown in Fig. 2.…”
Section: Methodssupporting
confidence: 69%
See 3 more Smart Citations
“…The reason for this discrepancy is the approximation inherent in the volume velocity matching conditions used for the inlet and outlet plane of the blockage in the plane wave model. This is confirmed by comparing plane wave predictions with a full finite element model [20,21], which is also shown in Fig. 2.…”
Section: Methodssupporting
confidence: 69%
“…In this article, analysis is restricted to the plane wave region only and it will be shown that this is sufficient to recover the area ratio and the length of the blockage. Whilst it is attractive to make use of higher order modes, maybe to try and recover more information about the shape of the blockage, this has been found to be very difficult to do, even under very controlled laboratory conditions [20]. This is believed to be because higher order modes are very sensitive to the boundary conditions in a duct and this sensitivity makes it difficult to develop a reliable and robust technique suitable for use under less controlled conditions, such as sewer systems [20].…”
Section: Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…Given a single source with continuous spectrum against a background of isotropic and band-limited white Gaussian noise, azimuth angle estimation can be performed using a complex acoustic intensity estimator (CAIE, also known as an acoustic energy flux estimator), which is a maximumlikelihood detector, and an azimuth angle estimator that employs a single vector hydrophone, as discussed in [14]. The use of a complex acoustic intensity estimator is further discussed in [15][16][17]. In the presence of interference or multiple sources, the acoustic energy flux is a mixture of the signals from all the sources.…”
Section: Introductionmentioning
confidence: 99%